Computation of intermodulation distortion in RF MEMS variable capacitor circuits using moments - Tannir, Dani A. (2016)
This paper introduces a new technique for the efficient computation of intermodulation distortion in radio frequency circuits that contain microelectromechanical system (MEMS) variable capacitors using moments analysis. This method is applied to an extended harmonic balance formulation, which contains the nonlinear equations that describe the dynamic mechanical behavior of MEMS variable capacitors, in addition to the nonlinear electric circuit equations. As a result, the moments method becomes a general multi-domain simulation method for quantifying nonlinear intermodulation distortion, while presenting significant computational cost reduction over harmonic balance-based methods.